The Effect of Covid-19 on Remittance Economy of Nepal - Kafle, Hari Bol (Research Nepal Journal of Development Studies, 2021)
Remittance in Nepal before the Covid-19 outbreak was the largest source of microeconomic stability since it has contributed 26 percent of the total Gross Domestic Product. Indeed, it is a principal income of the workers’ household since 55.8 percent of the Nepalese households have been receiving it. As expected, the potential inflow of remittance after Covid-19 decreased massively and it has an unprecedented adverse effect on the overall Nepalese economy, downsizing from national-level income to everyday living patterns of rural Nepal. The paper aims to analyses the present economic condition based on qualitative review. It is a qualitative review of the literature presented in reference. This study has scrutinized the primary level effects of Covid-19 in the remittance economy and figured out its chain of effects on key socioeconomic elements. Moreover, this study has revealed the role of remittance in Nepal and its primary level potential effects from the national level to the socio-economic life of rural Nepal. The reports published from Nepal Rastra Bank, Ministry of Finance, other authoritative agencies, and previous research works have been appraised.